2021
DOI: 10.15575/psy.v7i2.7159
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Tipe Self-Presentation melalui Konten Foto Instagram pada Mahasiswi

Abstract: Instagram is one popular social media that is used, especially among college students. Students tend to do self-presentations to give a good impression to others. This study is conducted using qualitative method to obtain description of the type of students’ self-presentation through photo contents uploaded to their Instagram account. The data was collected from the social media of 10 female college students of Faculty of Communication in Padjadjaran University. The results show that the types of self-presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Research shows that adolescents in doing self-presentation on social media display things that are not in accordance with the daily lives of adolescents. Smith and Sanderson (2015) and Fullwood, James, and Chen-Wilson (2016) and Felita, et al (2016), they revealed that when interacting in social media, adolescents are more likely to present a "good" self in accordance to the standards present in social media or the ideal self (Ridha Rahmah et al, 2019;Yang & Bradford Brown, 2016a;Hendraswara et al, 2021;Chua & Chang, 2016;Salim et al, 2017b;Yau & Reich, 2019). TikTok as a "fun" platform supports each other in supporting "be yourself" attitudes, normalising the expression of positive and difficult emotions and experiences (Jande & Ibrahim, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that adolescents in doing self-presentation on social media display things that are not in accordance with the daily lives of adolescents. Smith and Sanderson (2015) and Fullwood, James, and Chen-Wilson (2016) and Felita, et al (2016), they revealed that when interacting in social media, adolescents are more likely to present a "good" self in accordance to the standards present in social media or the ideal self (Ridha Rahmah et al, 2019;Yang & Bradford Brown, 2016a;Hendraswara et al, 2021;Chua & Chang, 2016;Salim et al, 2017b;Yau & Reich, 2019). TikTok as a "fun" platform supports each other in supporting "be yourself" attitudes, normalising the expression of positive and difficult emotions and experiences (Jande & Ibrahim, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Among university students, this social platform is used for surveillance, followed by documentation, coolness, and creativity (Sheldon & Bryant, 2016). In Indonesia, students employ various self-presentation strategies to make positive impressions on other Instagram users (Hendraswara et al, 2020). By exploring the potential of mindfulness traits, the effect of cyber-ostracism in the context of interactions on Instagram on mental conditions can be mapped before it develops into maladaptive behavioral choices, such as antisocial and withdrawal behaviors.…”
Section: Introductionmentioning
confidence: 99%